Recent advances in petrochronology: from dates to ages and rates of deep orogenic processes - Labrousse, Loic; Bonnet, Guillaume; François, Camille; Godet, Antoine; Gyomlai, Thomas (Comptes Rendus. Géoscience)
In order to decipher the prevalent processes active at depth in orogenic systems, their time sequence and their rates have to be assessed. This is essentially done via absolute dating of accessory and rock-forming metamorphic minerals. The interpretation of dates, now produced in high quantities and low uncertainties, with geochemical and textural information thanks to in situ dating techniques, into ages with a geological meaning, is based on sophisticated multi-disciplinary approaches. The wealth of data produced during the last decades in internal zones of mountain chains today questions some of the seminal concepts in geodynamics as well as in petrochronology. The concept of closure temperature [Jäger, 1967] but also the notions of metamorphic unit or metamorphic event are now to be considered in the light of campaign-style dating projects, that enable a comprehensive and statistical interpretation of age patterns from the mineral scale to the geodynamic process scale.